2015
DOI: 10.1021/acs.jced.5b00281
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamics and Kinetics of Heavy Metals Adsorption on Silica Particles Chemically Modified by Conjugated β-Ketoenol Furan

Abstract: A novel adsorbent for heavy metals, functionalized with conjugated β-ketoenol Furan, was fabricated using a simple heterogeneous method. The adsorbent design (SiNFn) was well analyzed and characterized by the techniques of solid state 13 C NMR, Fourier transform-infrared spectroscopy (FT-IR), elementary analysis, nitrogen adsorption−desorption isotherm, BET surface area, BJH pore sizes, and scanning electron microscopy (SEM). The new surface has good thermal stability determined by thermogravimetry curves anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
23
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 62 publications
(26 citation statements)
references
References 77 publications
3
23
0
Order By: Relevance
“…The 3-aminopropylsilica (SiNH 2 ) material was prepared using our recently reported method [14][15][16][17][18][19].…”
Section: Synthesis Of 3-aminopropylsilica (Sinh 2 )mentioning
confidence: 99%
See 2 more Smart Citations
“…The 3-aminopropylsilica (SiNH 2 ) material was prepared using our recently reported method [14][15][16][17][18][19].…”
Section: Synthesis Of 3-aminopropylsilica (Sinh 2 )mentioning
confidence: 99%
“…It has been found that the behavior of these hybrid materials used as an adsorbent is mainly dependent on the presence of β-keto-enol group embedded with heterocyclic moieties, which afford the molecule with the ability to form strong interactions with metal ions [14,15].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, we have reported some new heterocyclic keto-enol compounds that have shown remarkable biological activities [7] and e cient coordination properties [8,9]. Herein, we report a β-keto-enol compound: (Z)-1-(1,5-dimethyl-1H-pyrazol-3-yl)-3-hydroxy-3-phenylprop-2-en-1-one, prepared in acceptable yield.…”
Section: Discussionmentioning
confidence: 98%
“…Owing to these properties, silica nanoparticles and functionalized silica nanoparticles have been used in the past for the removal of toxic metal ions. For example, Fe 3 O 4 @SiO 2 core–shell nanoparticles functionalized with phenyl isothiocyanate, ammonium (4‐chloro‐2‐mercaptophenyl)carbamodithioate immobilized on mesoporous silica, 4‐dodecyl‐6‐((4‐(hexyloxy)phenyl)diazenyl)benzene‐1,3‐diol‐coated mesoporous silica, 1E,1′E,1′′E,1′′′E‐(tetrakis(3‐carboxysalicylidene))naphthalene‐1,2,5,5‐tetramine immobilized on mesoporous silica monoliths, 4‐ tert ‐octyl‐4‐((phenyl)diazenyl)phenol‐functionalized inorganic mesoporous silica, β‐ketoenolfuran immobilized on silica nanoparticles, 5,5′‐(1,4‐phenylenebis(diazene‐2,1‐diyl))bis(2,4‐dihydroxybenzaldehyde) and 5,5′‐(1,3‐phenylenebis(diazene‐2,1‐diyl))bis(2,4‐dihydroxybenzaldehyde) supported with amino‐modified silica gel have been successfully applied for the adsorption of lead ions.…”
Section: Introductionmentioning
confidence: 99%